Case Report: A rare transthyretin mutation p.D58Y in a Chinese case of transthyretin amyloid cardiomyopathy - Lin, Jibin; Peng, Jiangtong; Lv, Bingjie; Cao, Zheng; Chen, Zhijian (Frontiers in Cardiovascular Medicine, 2024)
Hereditary transthyretin amyloid (ATTRv) cardiomyopathy (CM) is cause by mutations in the TTR gene.TTR mutations contribute to TTR tetramer destabilization and dissociation, lead to excessive insoluble amyloid fibrils deposition in the myocardium and finally result in cardiac dysfunction. In this article, we report one Chinese transthyretin mutation p.D58Y case and provide detailed cardiac amyloidosis information, including transthoracic echocardiography, cardiac magnetic resonance and SPECT imaging for the first time. Our report here would help better understand ATTR genotypes and phenotypes.